Análise do carregamento elétrico veicular pelo sistema fotovoltaico off-grid - Todeschini, Fábio Mateus (My University, 2024)
This study presents an analysis of electric vehicle charging stations (eletropostos) based on off-grid solar systems. The integration of electric vehicles with photovoltaic energy systems shows positive potential, being able to efficiently charge these vehicles. In this context, it is essential to calculate the capacity of off-grid photovoltaic systems, ensuring adequate infrastructure for the installation of solar modules and charging points. The analysis considers the complementarity of these systems in different regions of the country, taking into account the energy consumption for vehicle recharging, the correct sizing without access to the electrical grid, the available electric vehicle models, their consumption and range, as well as a cost comparison across various regions of Brazil. The developed methodology analyzed the implementation of off-grid charging stations in the five regions of Brazil and their results. It was concluded that the viability of off-grid charging stations is challenging, with long payback periods and low returns on investment (ROI), especially in the short and medium term. The Northeast region proved to be more favorable due to lower costs and higher energy efficiency, while the South presented greater challenges due to the need for more batteries and modules. To increase economic viability, it is recommended to negotiate better equipment prices, seek tax incentives, diversify services offered at the charging stations, and form strategic partnerships. Proper implementation can promote energy sustainability, although current conditions still present significant challenges. [resumo fornecido pelo autor]
Este estudo apresenta uma análise de eletropostos baseados em sistemas solares off-grid. A integração de veículos elétricos com sistemas de energia fotovoltaica mostra potencial positivo, sendo capaz de carregar esses veículos de maneira eficiente. Nesse contexto, é essencial calcular a capacidade de sistemas fotovoltaicos off-grid, assegurando a infraestrutura adequada para a instalação de módulos solares e pontos de recarga. A análise considera a complementaridade desses sistemas em diferentes regiões do país, levando em conta o consumo de energia para recarga veicular, o dimensionamento correto sem acesso à rede elétrica, os modelos de veículos elétricos disponíveis, seu consumo e autonomia, além de uma comparação de custos em várias regiões do Brasil. A metodologia desenvolvida analisou a implementação de eletropostos off-grid nas cinco regiões do Brasil e seus resultados. Concluiu-se que a viabilidade dos eletropostos off-grid é desafiadora, com longos períodos de payback e baixos retornos sobre investimento (ROI), especialmente no curto e médio prazo. A região Nordeste mostrou-se mais favorável devido aos menores custos e maior eficiência energética, enquanto o Sul apresentou maiores desafios devido à necessidade de mais baterias e módulos. Para aumentar a viabilidade econômica, recomenda-se negociar melhores preços para equipamentos, buscar incentivos fiscais, diversificar serviços oferecidos nos eletropostos e formar parcerias estratégicas. A implementação adequada pode promover a sustentabilidade energética, embora as condições atuais ainda apresentem desafios significativos. [resumo fornecido pelo autor]
Keywords: Engenharia elétrica; Automóveis elétricos; Sistemas de energia fotovoltaica; Energia - Armazenamento